From Plants to Planet: A Review of the Emerging Role of Botany in Human Health, Climate Resilience and Sustainable Development - Jyoti Kawalekar; Adarsh Pundalik (International Journal For Multidisciplinary Research, 2026)
Abstract Plants are fundamental to human civilization, providing food, medicines, oxygen, fibres, raw materials and ecosystem services. Their importance extends to environmental quality, human health, livelihoods, culture and community resilience. With climate change, urbanization and biodiversity loss creating new challenges, Botany has an increasingly important role in addressing human and environmental needs. Medicinal plants provide an important link between plant diversity and healthcare through their biologically active secondary metabolites and traditional uses. However, climate change, habitat degradation and unsustainable harvesting may alter their distribution, productivity and phytochemical composition. Urban green spaces, botanical gardens and community gardens also contribute to biodiversity conservation, climate adaptation, environmental quality and human well-being. This review examines the relationship between plants, human welfare and environmental resilience, focusing on medicinal plants, climate change, urban green spaces, biodiversity conservation and community participation. It emphasizes integrating traditional knowledge with modern botanical research and sustainable conservation. A people-centered and interdisciplinary approach to Botany can transform plant knowledge into practical solutions for healthier, resilient and sustainable communities.